Membrane vesicles released by Lacticaseibacillus casei BL23 inhibit the biofilm formation of Salmonella Enteritidis - David da Silva Barreira; Julie Laurent; Jessica Lourenço; Julia Novion Ducassou; Yohann Couté; Jean Guzzo; Aurélie Rieu (Scientific Reports, 2023)
Abstract Biofilms represent a major concern in the food industry and healthcare. The use of probiotic bacteria and their derivatives as an alternative to conventional treatments to fight biofilm development is a promising option that has provided convincing results in the last decades. Recently, membrane vesicles (MVs) produced by probiotics have generated considerable interest due to the diversity of roles they have been associated with. However, the antimicrobial activity of probiotic MVs remains to be studied. In this work, we showed that membrane vesicles produced by Lacticaseibacillus casei BL23 (LC-MVs) exhibited strong antibiofilm activity against Salmonella enterica serovar Enteritidis (S. Enteritidis) without affecting bacterial growth. Furthermore, we found that LC-MVs affected the early stages of S. Enteritidis biofilm development and prevented attachment of bacteria to polystyrene surfaces. Importantly, LC-MVs did not impact the biomass of already established biofilms. We also demonstrated that the antibiofilm activity depended on the proteins associated with the LC-MV fraction. Finally, two peptidoglycan hydrolases (PGHs) were found to be associated with the antibiofilm activity of LC-MVs. Overall, this work allowed to identify the antibiofilm properties of LC-MVs and paved the way for the use of probiotic MVs against the development of negative biofilms.